A Rare Cause of Secondary Postpartum Hemorrhage: Uterine Scar Dehiscence with Cervico-Isthmic Laceration After Repeat Cesarean Section - Berns, Annike Ida; Ayuandari, Sarrah; Maliki, Fauzan Achmad; Prawitasari, Shinta; Ariffianto, Adi (JURNAL KESEHATAN REPRODUKSI, 2026)
To describe a rare and atypical case of secondary postpartum hemorrhage (PPH) induced by uterine scar dehiscence in conjunction with an unexplained uterine laceration in the cervico-isthmic region. We report the case of a 29-year-old woman, gravida 2 para 2, who had significant vaginal bleeding and signs of hemorrhagic shock 10 days post-repeated cesarean section. The bleeding was not controlled despite initial resuscitation and medical care. Transabdominal ultrasonography revealed signs of pathology at the previous cesarean scar site. Due to persistent hemodynamic instability, an emergency laparotomy was conducted, exposing active hemorrhage from uterine scar dehiscence, as well as a laceration extending caudally into the cervico-isthmic area, without a clearly identifiable cause. Definitive management required total hysterectomy to achieve hemostasis. This case highlights the importance of consideration of structural causes when medical treatment fails, as early surgical intervention can be life-saving.